ARENAS, REPERTÓRIOS E AÇÕES: o processo de tentativa de implantação do Terminal Portuário de São Luís, no povoado Cajueiro - MOREIRA, Jadeylson Ferreira (2015)
This dissertation is embedded in socio-environmental conflicts and object the experience of political mobilization of the cashew tree located in the village Rural II of São Luís do Maranhão, in the neighborhood of the complex Port of Saint Louis. Analyzes the resistance movement of the village threatened by the installation of the port Terminal of Saint Louis, the WRP Management company of ports and terminals LTDA. in this context, the study attempts to reconstruct the process of resistance that generated a series of class-action suits from alliances made with neighbouring settlements, institutions linked to the Federal University of Maranhão, Church Catholic actors local politicians, social movements and entities. The analysis turns to the issue of arena, mediated by power relations about space in dispute, having as focus, the proposed installation of the extractive reserve of Tauá-Mirim. Still, the analysis considers the repertories of collective action, accumulated by the actors throughout the process of social resistance in areas threatened by the process of expansion of logistics infrastructure describing the forms of action employed between the months of July 2014 and February 2015. 15 meetings were analysed, 03 public hearings, 04 08 interviews and demonstrations. In addition to magazines, reports, production reports, newspapers, TV programs, and master plan documents on the legal question of the cashew tree. We tried to give visibility to forms of mobilisation of actors and their performances that revealed the importance of movement formed around the community.